ANALISIS PROGRAM PENDAMPINGAN UMKM PADA PT BANK BTPN SYARIAH TERHADAP KESEJAHTERAAN NASABAH DI KABUPATEN NGAWI - Nura Yulianti; Fauzatul Laily Nisa (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
In the current era of globalization, development heavily relies on the economic sector. SMEs are often depicted as playing a significant role in Indonesia's economy. Achieving good economic outcomes can be realized by maximizing income. One way to boost SMEs' income is through optimal mentoring. With a large number of PT Bank BTPN Syariah customers consisting of productive underprivileged mothers and micro-entrepreneurs, PT Bank BTPN Syariah provides mentoring facilitators to help them achieve their goals. The role of these facilitators is to assist customers in increasing sales, ultimately leading to higher income. To achieve this goal, a contextual approach method is used by providing theoretical material first, tailored to the customers' businesses, in the form of videos and presentations from BTPN Syariah, followed by practical application. The result of this activity is an enhanced understanding among customers about tips, methods, and marketing strategies through social media and marketplace platforms, with the expectation of boosting sales.